2015
DOI: 10.1088/1674-1056/24/6/063701
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for formation and trapping of the two-ion Coulomb cluster in the dissipative optical superlattice

Abstract: Conditions have been studied under which a polychromatic optical superlattice can form and trap the Coulomb cluster of two strongly interacting ions. In our previous work (Krasnov I V and Kamenshchikov L P 2014 Opt. Comm. 312 192) this new all-optical method of obtaining and confining the Coulomb clusters was demonstrated by numerical simulations for special values of the optical superlattice parameters and in the case of Yb ions. In the present paper the conditions are explicitly formulated, under which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Du [22] found that the q-exponential of a sum can be applied as the product of the q-exponential based on the probabilistically independent postulate employed in nonextensive statistical mechanics. Krasnov [23] also found q-exponential type velocity distribution of the ions in the optical superlattice. Chen et al [24] presented a new method based on the q-exponential distribution to suppress the noise and increase the accuracy of feature extraction for ultrasonic Lamb wave signals.…”
Section: Discussionmentioning
confidence: 86%
“…Du [22] found that the q-exponential of a sum can be applied as the product of the q-exponential based on the probabilistically independent postulate employed in nonextensive statistical mechanics. Krasnov [23] also found q-exponential type velocity distribution of the ions in the optical superlattice. Chen et al [24] presented a new method based on the q-exponential distribution to suppress the noise and increase the accuracy of feature extraction for ultrasonic Lamb wave signals.…”
Section: Discussionmentioning
confidence: 86%
“…The detailed discussion of equations ( 2) and ( 3) and physical sense of different terms of this equation is included into [14][15][16]. Here, we only note some key factors important for understanding the results of our simulations.…”
Section: Trapping and Friction Forces Acting On The αTh Ion;mentioning
confidence: 99%
“…The parameter ζ = s 0 /ω R L (the analogue of the Knudsen number of problem [16]) is small, therefore, the particle motion is overdamped [14,15].…”
Section: Trapping and Friction Forces Acting On The αTh Ion;mentioning
confidence: 99%
See 2 more Smart Citations